ENT 600 : Neo Scan Sdn Bhd / Atasya Syuhada Mohamad ...[e al.] - Mohamad, Atasya Syuhada; Md Shapari, Mohd Haziq Asfa; Mohd, Nurul Hidayatul Amyra; Ungku Ibrahim, Ungku Ainaa Ul-Mardhlah (2018)
NeoScan Sdn Bhd is a new company established in October 2018 with a big vision "To produce the best friendly and high quality printing machines in the world". Our company focus on bringing friendly and time saving printer especially for students and workers. We have created a Pen Printer that make printing become more easier and cost effective. Our product features consisting of ink transferring technology, flexible waterproof circuit and USB power source. This features inside the printer make it safe to use at any conditions. This product was engineered and design toward providing a user friendly printing machine. Most of existing printer in current market use ink cartridges that are specifically made for the printer which can cost a lot especially for students in college. The price for ink cartridges in Malaysia can be ranging from RM30 to RM 300 depending on the quality of the ink. We have taken one step further from the competitors by introducing Pen Printer. We strongly believe that our product can go further by keep on focusing on research and development to improve our product quality, so that we can sustain in the market as nowadays, people are looking forward and interested to try new and friendly technology..